Ethnoscience Learning Ideas Oriented to Outcome Base Education (OBE) to Foster Entrepreneurial Competency - Khery, Yusran; Hakim, Aliefman; Rokhmat, Joni; Sukarso, AA (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study recommends OBE-oriented ethnoscience learning to foster entrepreneurial competence carried out with 6 stages of learning namely ethnoscience observation activities. ethnoscience analysis, product ideas, production trials, production cost analysis and product presentation/presentation. This learning model is further introduced by the author as ethnoedusciencepreneurship. This learning step is relevant to the main outputs/outcomes of science learning, namely Content Knowledge (HBS1): Inquiry Skills and Scientific Processes (HBS2): Laboratory Engineering and Safety (HBS3): Science Communication (HBS4): Critical Thinking and Problem Solving (HBS5): Scientific Literacy and Ethical Considerations (HBS6): Lifelong Learning and Scientific Investigation (HBS7). The learning step can accommodate the needs of developing entrepreneurial competencies in students referring to SKKNI Number 53 of 2014 concerning Industrial Entrepreneurship.